Is Celiac Disease an Etiological Factor in Children with Nonsyndromic Intellectual Disability?. (March 2016) - Sezer, Taner; Balcı, Oya; Özçay, Figen; Bayraktar, Nilufer; Alehan, Füsun
To determine the prevalence of celiac disease in children and adolescents with nonsyndromic intellectual disability, we investigated serum levels of tissue transglutaminase antibody and total IgA from 232 children with nonsyndromic intellectual disability and in a healthy control group of 239 children. Study participants who were positive for tissue transglutaminase antibody underwent a duodenal biopsy. A total of 3 patients in the nonsyndromic intellectual disability group (5.45%) and 1 in the control group (0.41%) had positive serum tissue transglutaminase antibody ( P > .05). Duodenal biopsy confirmed celiac disease in only 1 patient who had nonsyndromic intellectual disability. In this present study, children with nonsyndromic intellectual disability did not exhibit a higher celiac disease prevalence rate compared with healthy controls. Therefore, we suggest that screening test for celiac disease should not be necessary as a part of the management of mild and moderate nonsyndromic intellectual disability. However, cases of severe nonsyndromic intellectual disability could be examined for celiac disease.